2019
DOI: 10.1111/exd.14053
|View full text |Cite
|
Sign up to set email alerts
|

Fas‐FasL interaction in cytotoxic T cell‐mediated vitiligo: The role of lesional expression of tumor necrosis factor‐α and interferon‐γ in Fas‐mediated melanocyte apoptosis

Abstract: Vitiligo is an acquired skin depigmentation disorder resulting from the selective loss of epidermal melanocytes, and previous studies have suggested that a T lymphocyte‐mediated mechanism has a role in melanocyte loss. Although Fas‐Fas ligand (FasL) interactions are important for T lymphocytes to mediate cytotoxicity, there are only few reports examining the involvement of the Fas‐FasL pathway in vitiligo using in vivo mouse models. In addition, there have been no reports concerning Fas‐mediated apoptosis in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…HSP70‐exposed TNF related apoptosis‐inducing ligand (TRAIL) + DC are lytic towards TRAIL‐receptor‐expressing melanocytes 141,142 . Cells expressing TRAIL are also found to infiltrate the papillary dermis of patients with inflammatory vitiligo 143 . Besides, upon endogenous and exogenous stress, NK, and ILC1 secret IFN‐γ to induce expression of C‐X‐C motif chemokine receptor (CXCR) 3B on melanocyte surface and release of CXCL9, CXCL10, and CXCL11 from keratinocyte and melanocyte.…”
Section: Innate Immune Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP70‐exposed TNF related apoptosis‐inducing ligand (TRAIL) + DC are lytic towards TRAIL‐receptor‐expressing melanocytes 141,142 . Cells expressing TRAIL are also found to infiltrate the papillary dermis of patients with inflammatory vitiligo 143 . Besides, upon endogenous and exogenous stress, NK, and ILC1 secret IFN‐γ to induce expression of C‐X‐C motif chemokine receptor (CXCR) 3B on melanocyte surface and release of CXCL9, CXCL10, and CXCL11 from keratinocyte and melanocyte.…”
Section: Innate Immune Activationmentioning
confidence: 99%
“…Research based on a mouse model with DNA immunization against a xenogeneic form of TRP‐2 revealed that autoimmunity against normal melanocytes required perforin but Fas–FasL was dispensable 166 . Of the other three studies, depending on transgenic mice with tyrosinase‐specific T cell clone, 167 transgenic mice carrying T cells with an HLA‐A2 restricted human tyrosinase reactive T cell receptor (TCR) 168 and mice manifesting melanoma‐induced autoimmune symptoms (vitiligo‐like white coat), 143 respectively, the former two regard perforin as an unnecessary mechanism in melanocyte destruction. And the first and third affirmed the implication of the Fas–FasL system in killing melanocyte.…”
Section: Adaptive Immune Activationmentioning
confidence: 99%
“…T lymphocyte‐mediated mechanism has been strongly suggested to play a great role in the loss of MCs. Cytotoxic T lymphocytes (CTLs) can directly induce cytotoxicity in MCs through release of cytotoxic mediators such as tumor necrosis factor (TNF)‐α, interferon as well as Fas‐FasL interaction (Jimbo et al., 2019). As a death receptor interacting with FasL, Fas recruits the adaptor protein Fas‐associated protein with death domain (FADD) and procaspase‐8 to form a death‐inducing signaling complex (DISC) in which procaspase‐8 is cleaved and activated.…”
Section: Conventional Forms Of Cell Death In Vitiligomentioning
confidence: 99%
“…Activated caspase‐8 then results in the proteolytic stimulation of downstream effector caspases, such as caspases‐3 and caspases‐7, finally inducing apoptosis. One study (M. Li et al., 2008) demonstrated that polymorphisms of the FAS gene may influence the risk and clinical progression of vitiligo in Han Chinese populations and elevated level of Fas was indeed observed in vitiligo MCs (Jimbo et al., 2019). Moreover, alteration of cytokine expression has been demonstrated in vitiligo patients.…”
Section: Conventional Forms Of Cell Death In Vitiligomentioning
confidence: 99%
See 1 more Smart Citation